Protein-nucleic Acid Interactions : Structural Biology - Rice, Phoebe A; Ed (Royal Society of Chemistry, 2008)
Written by a team of experts, this book bridges the gap between the DNA- and RNA- views of protein-nucleic acid recognition which are often treated as separate fields.